PENERAPAN STRATEGI PEMASARAN, INOVASI PRODUK KREATIF DAN ORIENTASI PASAR UNTUK MENINGKATKAN KINERJA PEMASARAN UMKM - Elwisam, Elwisam; Lestari, Rahayu (Economic Faculty, Attahiriyah Islamic University, 2019)
This research discusses issues concerning with the performance of marketing of micro and small entrepreneurs at the South Tangerang - Banten. Data were collected from 65 respondents, and PLS-SEM was used as an analysis tool. The results show that creative product innovation, market orientation, and marketing strategies have a positive effect on marketing performance. In addition, business development also proved to have an effect on marketing performance. Implications and suggestions are described in this paper. Keywords: marketing strategies, creative product innovations, market orientation